Strategi Pemeliharaan Sarana Prasarana Pendidikan Islam di Pondok Pesantren Ziyadatut Taqwa Larangan Tokol - Moh. Afiful Khair (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Infrastructure can support a learning process, therefore management definitely requires maintenance of facilities in order to improve the quality of infrastructure at the Ziyadatut Taqwa Islamic boarding school. Infrastructure facilities explain maintenance which is currently in Islamic boarding schools as a learning tool and tool. media that must really be managed as well as possible, the aim of this research is to be able to find out the infrastructure used at the Ziayadatut Taqwa Islamic boarding school, the prohibition of Pamekasan shops in order to maintain existing infrastructure, this method uses qualitative because it is through an interview or Direct observation of the location using this qualitative method means that we can maintain the infrastructure at the Ziyadatut Taqwa Ban Tokol Pamekasan Islamic boarding school effectively and efficiently.